Serum PlGF and EGF are independent prognostic markers in non-metastatic colorectal cancer - Schölch, Sebastian; Rahbari, Mohammad; Schneider, Martin; Reißfelder, Christoph; Rahbari, Nuh Nabi (Scientific reports, 2019)
The aim of this study was to determine the prognostic value of circulating angiogenic cytokines in non-metastatic colorectal cancer (CRC) patients. Preoperative serum samples of a training (TC) (n = 219) and a validation cohort (VC) (n = 168) were analyzed via ELISA to determine PlGF, EGF, VEGF, Ang1, PDGF-A, PDGF-B, IL-8 and bFGF levels. In addition, survival was correlated with PlGF and EGF expression measured by microarray and RNAseq in two publicly available, independent cohorts (n = 550 and n = 463, respectively). Prognostic values for overall (OS) and disease-free survival (DFS) were determined using uni- and multivariate Cox proportional hazard analyses. Elevated PlGF is predictive for impaired OS (TC: HR 1.056; p = 0.046; VC: HR 1.093; p = 0.001) and DFS (TC: HR 1.052; p = 0.029; VC: HR 1.091; p = 0.009). Conversely, elevated EGF is associated with favorable DFS (TC: HR 0.998; p = 0.045; VC: HR 0.998; p = 0.018) but not OS (TC: p = 0.201; VC: p = 0.453). None of the other angiogenic cytokines correlated with prognosis. The prognostic value of PlGF (OS + DFS) and EGF (DFS) was confirmed in both independent retrospective cohorts. Serum PlGF and EGF may serve as prognostic markers in non-metastatic CRC.